2007
DOI: 10.1063/1.2712298
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect in layer structural Gd5(SixGe1−x)4∕Gd composite material

Abstract: A series of layer structural composite magnetic refrigerant materials with composition of (Gd5Si2Ge2)x(Gd)y(Gd5Si1.85Ge2.15)z was synthesized via spark plasma sintering technique. The adiabatic temperature change (ΔTad) of the composites and of the three individual components was measured directly from 245to315K with a magnetic field change of 1.5T using a homemade magnetocaloric effect measuring apparatus. For all composites with different x:y:z ratios, their resultant ΔTad uniformly peaks at 246, 276, and 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…As shown in the table, the Mn atoms occupy the 3g sites and some 3f sites, the Fe atoms occupy the rest of the 3f sites, while P and the Ge atoms randomly occupy the 2c and 1b sites. 10 Although the ⌬T ad of the compound was theoretically determined by its heat capacity, the absence of the magnetic field induced first-order phase transition is mainly responsible for the low ⌬T ad of the compound. Figure 2 shows the temperature dependence of the magnetization of bulk Mn 1.1 Fe 0.9 P 0.8 Ge 0.2 alloy measured in a magnetic field of 0.05 T. It should be noted that the virgin effect, which had been found in first time cooling of as-prepared MnFePGe alloy by some previous investigations, 1,3 does exist in our sample.…”
mentioning
confidence: 99%
“…As shown in the table, the Mn atoms occupy the 3g sites and some 3f sites, the Fe atoms occupy the rest of the 3f sites, while P and the Ge atoms randomly occupy the 2c and 1b sites. 10 Although the ⌬T ad of the compound was theoretically determined by its heat capacity, the absence of the magnetic field induced first-order phase transition is mainly responsible for the low ⌬T ad of the compound. Figure 2 shows the temperature dependence of the magnetization of bulk Mn 1.1 Fe 0.9 P 0.8 Ge 0.2 alloy measured in a magnetic field of 0.05 T. It should be noted that the virgin effect, which had been found in first time cooling of as-prepared MnFePGe alloy by some previous investigations, 1,3 does exist in our sample.…”
mentioning
confidence: 99%
“…Another approach for MCE enhancement is layered structure composites which though exhibiting larger temperature span covering a large working temperature range didn't enhanced the MCE properties [22,23]. The first example is synthesized from a binary composite Gd x-(Gd 5 Si 2 Ge 2 ) 1−x (where x = 0.3, 0.5, 0.7) by SPS technique [22].…”
Section: Gd 5 (Si 2 Ge 2 )mentioning
confidence: 99%
“…Recent calculations have shown that RC of magnetic refrigerants can be enhanced using multiphase materials or composites, which expand the temperature range over which a significant magnetic entropy change can be obtained [11,12]. In particular, von Ranke et al proposed a theoretical investigation on MCE in MnAs 1 À x Sb x [10] composite.…”
Section: Introductionmentioning
confidence: 98%
“…This condition is difficult to be accomplished by a single material. To overcome this limitation, composite materials formed by associating different magnetic materials with close transition temperatures, T C 0 s, have been extensively suggested in the literature [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%